Gravity and strings - Ortin Tomas (Cambridge CUP, 2004)
In Part I, the foundations are traced back to the very early special-relativistic field theories of gravity, showing how such theories lead to general relativity. Gauge theories of gravity are then discussed and used to introduce supergravity theories. I
Keywords: Quantum gravity; String models